Isolated Spontaneous Renal Artery Dissection: A Case Report and Review - Tandon, Gaurav; Sukhija, Rishi (International Journal of Angiology, 2012)
We report an interesting case of a 65-year-old gentleman who presented with hypertensive emergency and was found to have an isolated spontaneous dissection of the right renal artery. The dissection was stented via endovascular approach and resulted in marked improvement in blood pressure. Spontaneous renal artery dissection is a difficult condition to diagnose and treat, unless suspected early enough during the course of treatment. Endovascular intervention is the treatment of choice, as failure of conservative treatment may have long lasting clinical implications relating to decreased renal perfusion. Surgical intervention can be associated with high rate of complications.
Keywords: renal artery obstruction; renovascular hypertension